2013
DOI: 10.3168/jds.2013-6680
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic acid increased yields of milk and milk fat and nutrient digestibility across production level of lactating cows

Abstract: The effects of palmitic acid supplementation on feed intake, digestibility, and metabolic and production responses were evaluated in dairy cows with a wide range of milk production (34.5 to 66.2 kg/d) in a crossover design experiment with a covariate period. Thirty-two multiparous Holstein cows (151 ± 66 d in milk) were randomly assigned to treatment sequence within level of milk production. Treatments were diets supplemented (2% of diet DM) with palmitic acid (PA; 99% C16:0) or control (SH; soyhulls). Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

61
154
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(230 citation statements)
references
References 35 publications
61
154
10
1
Order By: Relevance
“…In our previous experiment, PA decreased intake relative to a no-fat control, but was not different from Ca-FA . In addition, although not measured in the current experiment, plasma concentrations of gut peptides such as glucagon-like peptide 1 and cholecystokinin are often increased by unsaturated compared with saturated FA supplements (Relling and Reynolds, 2007;Bradford et al, 2008), and cholecystokinin was increased by a highly enriched palmitic acid supplement relative to no fat supplementation (Piantoni et al, 2013).…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…In our previous experiment, PA decreased intake relative to a no-fat control, but was not different from Ca-FA . In addition, although not measured in the current experiment, plasma concentrations of gut peptides such as glucagon-like peptide 1 and cholecystokinin are often increased by unsaturated compared with saturated FA supplements (Relling and Reynolds, 2007;Bradford et al, 2008), and cholecystokinin was increased by a highly enriched palmitic acid supplement relative to no fat supplementation (Piantoni et al, 2013).…”
mentioning
confidence: 59%
“…Piantoni et al (2013) reported approximately a 10% increase in plasma NEFA concentration and a tendency for increased plasma insulin concentration, but no change in plasma triglyceride concentration when feeding a highly enriched palmitic acid supplement compared with a no-supplemental-fat control. Previous investigations of saturated fat supplements lower in C16:0 and higher in C18:0 reported increased insulin and decreased NEFA concentrations compared with unsaturated FA (Harvatine and Allen, 2005;Relling and Reynolds, 2007).…”
mentioning
confidence: 95%
See 3 more Smart Citations